2012
DOI: 10.1097/qad.0b013e32834c4be4
|View full text |Cite
|
Sign up to set email alerts
|

HIV seroprevalence among orphaned and homeless youth

Abstract: One of four youths who were both homeless and orphaned was HIV-infected; these youths were significantly more likely to be HIV infected and to report injection drug use than those with adequate housing and living parents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 30 publications
1
31
1
Order By: Relevance
“…Considering the high prevalence of homelessness and public drug use among street-involved youth (DeMatteo et al, 1999; Marshall, Kerr, Qi, Montaner, & Wood, 2010; Rachlis, Wood, Zhang, Montaner, & Kerr, 2009), additional efforts to address these environmental determinants of risk among this subpopulation may be of greater benefit than efforts that focus solely on modifying individual behaviour. These include structural and environmental interventions that have demonstrated effectiveness in reducing harm and risk among youth and adult drug users, including the provision of stable housing opportunities, the establishment of supervised injection facilities, and improved access to drug and alcohol treatment centres (Frankish, Hwang, & Quantz, 2005; Hadland, Kerr, Li, Montaner, & Wood, 2009; Hillis et al, 2012; Stoltz et al, 2007). …”
Section: Discussionmentioning
confidence: 99%
“…Considering the high prevalence of homelessness and public drug use among street-involved youth (DeMatteo et al, 1999; Marshall, Kerr, Qi, Montaner, & Wood, 2010; Rachlis, Wood, Zhang, Montaner, & Kerr, 2009), additional efforts to address these environmental determinants of risk among this subpopulation may be of greater benefit than efforts that focus solely on modifying individual behaviour. These include structural and environmental interventions that have demonstrated effectiveness in reducing harm and risk among youth and adult drug users, including the provision of stable housing opportunities, the establishment of supervised injection facilities, and improved access to drug and alcohol treatment centres (Frankish, Hwang, & Quantz, 2005; Hadland, Kerr, Li, Montaner, & Wood, 2009; Hillis et al, 2012; Stoltz et al, 2007). …”
Section: Discussionmentioning
confidence: 99%
“…Studies 3,10,11,16,17,25,27 conducted in several different cities around the world showed that the prevalence of HIV infection among homeless people is signifi cantly higher than in the general population. In the present study, however, this rate was as high as in those population groups most affected by the HIV/AIDS epidemic in Brazil such as sex workers 23 (4.8%) and MSM 13 (13.6%).…”
Section: Discussionmentioning
confidence: 99%
“…A recent review of studies conducted in Ukraine indicated that youth who were homeless and orphaned were more likely to be HIV-positive and to engage in injecting drug use, compared to youth with stable housing who resided with their parents (40). In Western countries, adolescents have reported use of emerging drugs such as synthetic cannibinoids (e.g., “Spice”) and cathinones (e.g., “bath salts”), and over-the-counter cough medicine dextromethorphan has gained popularity in Thailand among middle and high school students (41).…”
Section: Drug-using Populations and The Hiv Epidemicmentioning
confidence: 99%